The role of treated wastewater in fostering sustainable urban agriculture in Addis Ababa, Ethiopia - Gizaw Ebissa; Hayal Desta; Aramde Fetene (Discover Water)
Abstract Bole-Lemi Industrial Park (BLIP) in Ethiopia is providing treated wastewater (TW) to farmers. However, it has never been assessed for its contribution to the sustainability of the agriculture system, and therefore, its impacts remain unknow. The objective of the research is therefore to understand the contribution of treated wastewater from BLIP to the sustainability of the agriculture by analyzing its nutrient concentrations used as fertilizer (such as nitrogen and phosphorus), assessing its water security contribution using the volume of water available for production during the dry season, and its economic contribution in saving fertilizer cost. Results indicated that the total amount of nitrogen and phosphorus recovered from the TW in one production season (3.5 months) are 53 kg and 1 kg respectively. These amounts of nutrients enable farmers to save 5,535 USD per production season. The volume of water available for irrigation for one season is 17,500m3. The available TW has transformative effects, converting 70 hectares of dry seasons (no rain) of idle land into productive ones. This practice not only enhances urban farming but also contributes significantly to the local economy. Farmers, benefiting from free water access, can manage to reduce their fertilizer costs by 28%. While this accessible resource opens doors for communities with limited resources to participate in urban farming, it is crucial to address long-term sustainability. Continuous monitoring of soil conditions is imperative to mitigate potential adverse impacts on soil and plant growth. Maintaining free access to treated wastewater is essential to ensure the continued success of urban agriculture.